Principal’s Leadership Roles in Strengthening Religious Values Within School Culture - Iman Garish Muhammad; Muhammad Fauzan; Zaki Ulien Nuha; Muhammad Iqbal (UII Darullughah Waddawah Pasuruan, 2026)
Religious culture significantly influences students’ character, particularly in Islamic-based schools, where the principal plays a key role in integrating religious values into school culture. This study examines how principal leadership fosters and strengthens these values. Using a qualitative approach and field study methods, data were gathered via in-depth interviews with purposively selected school principals. The interviews focused on leadership practices like the role of leadership, exemplary behavior patterns, the impact of leadership. Data analysis involved qualitative descriptive techniques, including reduction and interpretation. The findings show that principals strengthen religious culture through structured policies integrated into daily, monthly, and annual activities. Their leadership involves setting an example, cultivate worship habits, encouraging moral behavior, coordinating with staff, engaging parents, and linking religious education with extracurricular activities. These efforts enhance students’ religious understanding, attitudes, and skills. The study concludes that effective principal leadership is vital for maintaining a strong religious culture. Key factors include consistent policy enforcement, exemplary conduct, ongoing supervision, and active parent participation, which collectively fortify religious values.